Carbonized cellulose microsphere@void@MXene composite films with egg-box structure for electromagnetic interference shielding. (February 2021) - Qian, Kunpeng; Zhou, Qianfan; Wu, Hongmin; Fang, Jianhui; Miao, Miao; Yang, Yuhuan; Cao, Shaomei; Shi, Liyi; Feng, Xin
Highlights: Carbonized cellulose microsphere@void@Ti3 C2 Tx MXene films were fabricated. The composite films with "egg-box" structure were designed for EMI shielding. Internal voids in films were conducive to increase multiple reflection of EMW. EMI SE was enhanced from 46.51 ± 0.04 dB to 59.76 ± 0.50 dB after carbonization. Abstract: Well established internal multilayered structures have been demonstrated to contribute greatly towards outstanding shielding effectiveness (SE) in electromagnetic interference (EMI) shielding systems. A specific encapsulation by intercalating carbonized cellulose microspheres into Ti3 C2 Tx MXene layers (CCM@MXene) is elaborately designed. The CCM@void@MXene composite films with "egg-box" structure are ultimately achieved by annealing treatment with spherical CCM@MXene as "egg" and Ti3 C2 Tx MXene layers as "box". The unique structure with interior void space is attributed to internal multiple reflections of incident electromagnetic waves (EMW) and contributes to the enhancement of EMW absorption. Thanks to the electrically conductive network of Ti3 C2 Tx MXene adhering to cellulose microspheres surface, the egg-box structure composite films exhibit superb electrical conductivity of 1672.0 ± 7.1 S cm −1 and excellent specific EMI shielding efficiency (up to 18637.14 dB cm 2 g −1 ) at an ultrathin thickness (12.1 ± 0.8 μm). This hierarchical porous egg-box structure offers an ideal potential for application in highly efficient EMI shielding systems.